A PEGylated alternating copolymeric prodrug of sulfur dioxide with glutathione responsiveness for Irinotecan delivery. Issue 1 (25th November 2020) - Zhang, Yu; Zhang, Hongyu; He, Pan; Yi, Xuan; Liu, Xinming; Xiao, Chunsheng
Abstract : An enhanced anticancer strategy combining the chemotherapy from Irinotecan with the oxidative damage from a sulfur dioxide polymer prodrug is presented. Abstract : In this study, an enhanced anticancer strategy combining the chemotherapy from antineoplastics with the oxidative damage from a sulfur dioxide (SO2 ) prodrug is presented. Based on the characteristics of a high glutathione (GSH) level in the tumor microenvironment, a novel GSH-responsive SO2 polymeric prodrug mPEG- b -P(PA- alt -GDNs) was designed and synthesized via a ring-opening alternating copolymerization and "click" reaction. The GSH-sensitive mechanism of the polymer was investigated in detail. Furthermore, Irinotecan was loaded into the polymeric prodrug nanoparticles by a self-assembly method with a drug loading content of 12.3 wt% and a loading efficiency of 42.2%. The drug-loaded nanoparticles showed a sensitive response to high concentrations of GSH in the tumor cells and rapidly released both Irinotecan and SO2 . The depletion of GSH and the release of SO2 were supposed to increase the level of reactive oxygen species in the tumor cell, which, in combination with the released Irinotecan, exerted an enhanced anti-proliferative effect against HepG2 cells. Finally, Irinotecan-loaded nanoparticles exhibited a stronger antitumor effect than free antineoplastics in HepG2 cells. Thus, these results indicated that our polymeric prodrug SO2 is a promising candidate for chemotherapeutic drug delivery and would be a new weapon in anticancer treatment.